New Labdanes with Antimicrobial and Acaricidal Activity: Terpenes of Callitris and Widdringtonia (Cupressaceae) - Nicholas J. Sadgrove; Haytham Senbill; Ben-Erik Van Wyk; Ben W. Greatrex (MDPI AG, 2020)
In spite of the evidence for antimicrobial and acaricidal effects in ethnobotanical reports of Callitris and Widdringtonia, the diterpene acids from Widdringtonia have never been described and no comparison to the Australian clade sister genus Callitris has been made. The critically endangered South African Clanwilliam cedar, Widdringtonia wallichii (syn. W. cedarbergensis), of the Cederberg Mountains was once prized for its enduring fragrant timbers and an essential oil that gives an aroma comparable to better known Mediterranean cedars, predominantly comprised by widdrol, cedrol, and thujopsene. In South Africa, two other 'cedars' are known, which are called W. nodiflora and W. schwarzii, but, until now, their chemical similarity to W. wallichii has not been investigated. Much like Widdringtonia, Callitris was once prized for its termite resistant timbers and an 'earthy' essential oil, but predominantly guaiol. The current study demonstrates that the essential oils were similar across all three species of Widdringtonia and two known non-volatile diterpene acids were identified in leaves: the pimaradiene sandaracopimaric acid (1) and the labdane Z-communic acid (2) with a lower yield of the E-isomer (3). Additionally, in the leaves of the three species, the structures of five new antimicrobial labdanes were assigned: 12-hydroxy-8R,17-epoxy-isocommunic acid (4), 8S-formyl-isocommunic acid (5), 8R,17-epoxy-isocommunic acid (6), 8R-17R-epoxy-E-communic acid (7), and 8R-17-epoxy-E-communic acid (8). Australian Callitris columellaris (syn. C. glaucophylla) also produced 1 and its isomer isopimaric acid, pisiferal (9), and pisiferic acid (10) from its leaves. Callitris endlicheri (Parl.) F.M.Bailey yielded isoozic acid (11) as the only major diterpene. Diterpenes 4-6, pisiferic acid (10), spathulenol, and guaiol (12) demonstrated antimicrobial and acaricidal activity.